A novel series of 4-methyl substituted pyrazole derivatives as potent glucagon receptor antagonists: Design, synthesis and evaluation of biological activities. Issue 8 (1st May 2018) - Shu, Shuangjie; Dai, Antao; Wang, Jiang; Wang, Bin; Feng, Yang; Li, Jia; Cai, Xiaoqing; Yang, Dehua; Ma, Dakota; Wang, Ming-Wei; Liu, Hong
Graphical abstract: Abstract: A novel series of 4-methyl substituted pyrazole derivatives were designed, synthesized and biologically evaluated as potent glucagon receptor (GCGR) antagonists. In this study, compounds 9q, 9r, 19d and 19e showed high GCGR binding (IC50 = 0.09 μM, 0.06 μM, 0.07 μM and 0.08 μM, respectively) and cyclic-adenosine monophosphate (cAMP) activities (IC50 = 0.22 μM, 0.26 μM, 0.44 μM and 0.46 μM, respectively) in cell-based assays. Most importantly, the docking experiment demonstrated that compound 9r formed extensive hydrophobic interactions with the receptor binding pocket, making it justifiable to further investigate the potential of becoming a GCGR antagonist.